Back and beyond New Zealand painting for the young and curious - O'Brien, Gregory 1961- (Auckland, New Zealand Auckland University Press, 2008)
A painting can take you many places. It ca take you around the world, or it can take you around the country, city or neighbourhood you live in. It can also transport you back to the time of myths, legends and ancient history -- or it can take you way into the future.

Since Maori first drew moa and mythical birds on cave walls, artists in Aotearoa New Zealand have provided an imaginative, lively account of the lives we've been leading, the dreams we've been dreaming and the stories we've been telling. Alongside works painted during the nineteenth and twentieth centuries, this book features art by contemporary painters and printmakers, all of them seasoned travellers across time and space. Kiwi, rugby players, angels and aunts, moa and mountains, the bush and the beaches all play starring roles in this birds-eye view of New Zealand painting. Back and beyond is alive with real and imagined encounters, with mysteries and discoveries, and with many of the paintings that have, over the past few hundred years, broadened the horizons of the citizens, young and old, of our shaky island nation.
Includes bibliographical references (p. 109-111)
New Zealand Post book of the year 2009, non-fiction winner.
Keywords: Painters -- New Zealand; Painting, New Zealand -- 20th century; Painting, New Zealand -- 21st century